Efficacy of atorvastatin-based treatment in super-aged patients with chronic subdural hematoma: a case series and literature review - Jiangyuan Yuan; Wei Quan; Xuanhui Liu; Pan Li; Jinhao Huang; Chuang Gao; Tao Liu; Yongqiang Zhang; Jianning Zhang; Rongcai Jiang; Rongcai Jiang (Frontiers in Neurology)
BackgroundChronic subdural hematoma (CSDH) is a common neurological disorder in the elderly, typically managed through surgical intervention; however, in patients aged 90 years and older, surgery is often not feasible due to comorbidities, anticoagulant use, and other age-related factors. This study evaluates the effects of atorvastatin, either as monotherapy or in combination with dexamethasone, in the conservative treatment of CSDH in patients over 90 years old, while also reviewing the current literature on the management of CSDH in this super-aged population.MethodsSeventeen super-aged patients diagnosed with CSDH at our neurosurgical department between January 2017 and June 2024, who either refused or were considered unsuitable for surgery, were included in the study. Six patients received atorvastatin monotherapy, while 11 were treated with a combination of atorvastatin and dexamethasone. Head imaging scans were analyzed, and the modified Rankin Scale (mRS) and Markwalder’s Grading Scale/Glasgow Coma Scale (MGS-GCS) scores were assessed before and after treatment.ResultsAt the six-month follow-up, all patients showed significant improvement in neurological symptoms, as reflected by lower mRS and MGS-GCS scores. Hematomas were completely absorbed in 10 patients, significantly reduced in five, and unchanged in two patients with calcified hematoma. Three patients developed hyperglycemia, and one patient exhibited transaminitis; these adverse effects were resolved following the discontinuation of dexamethasone and the use of hepatoprotective medications. No mortality was recorded during the six-month follow-up.ConclusionOur findings suggest that atorvastatin-based treatment may improve the prognosis of CSDH in super-aged patients and offer a viable therapeutic alternative for those ineligible for surgery.